Own Motivation, Peer Motivation, and Educational Success - Jan Bietenbeck (Center for Economic Studies and Ifo Institute (CESifo), 2020)
I study how motivation shapes own and peers' educational success. Using data from Project STAR, I find that academic motivation in early elementary school, as measured by a standardized psychological test, predicts contemporaneous and future test scores, high school GPA, and college-test taking over and above cognitive skills. Exploiting random assignment of students to classes, I find that exposure to motivated classmates causally affects contemporaneous reading achievement, a peer effect that operates over and above spillovers from classmates' past achieve-ment and socio-demographic composition. However, peer motivation does not affect longer-term educational success, likely because it does not change own motivation.
Keywords: I21; J13; J24; 330; motivation; personality; peer effects; Project STAR